Tensorized Label Learning Based Fast Fuzzy Clustering - Xue, Xingyu; Xue, Jingjing; Gao, Quanxue; Wang, Qianqian (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Multi-view graph clustering methods have been widely concerned due to the ability of dealing with arbitrarily shaped datasets. However, many methods with higher time and space complexity make them challenging to deal with large-scale datasets. Besides, many fuzzy clustering methods needs additional regularization terms or hyper-parameters to obtain the membership matrix or avoid trivial solutions, which weakens the model generalization ability. Furthermore, inconsistent clustering labels can arise when there are significant discrepancies between views, making it challenging to effectively leverage the complementary information from different views. To this end, we propose Tensorized Label Learning based Fast Fuzzy Clustering (TLLFFC). Specifically, we design a novel balanced regularization term to reduce pressure of tuning regularization parameters for fuzzy clustering. The label transmission strategy with the anchor graph makes TLLFFC suitable for large-scale datasets. Moreover, incorporating the Schatten p-norm regularization on the label matrices can effectively unearth the complementary information distributed among views, thereby align the labels across views more consistently. Extensive experiments verify the superiority of TLLFFC.